The Effect of Liquidity, Leverage, and Audit Committee on Sustainability Report Disclosure with Profitability as a Mediating Variable - Sonia, Devi; Khafid, Muhammad (Accounting Analysis Journal, 2020)
The purpose of this study is to obtain empirical evidence about the role of profitability in mediating the effect of liquidity, leverage, and company size to sustainability report disclosure. The population in this study were non-financial companies listed on the Indonesia Stock Exchange (IDX) in 2015-2017 from 465 companies. The sampling technique used purposive sampling method and produced a sample of 25 companies with 75 units of analysis. This study used path analysis with the help of IBM SPSS 21 software. The results of the analysis show that liquidity and leverage have a negative and significant effect on sustainability report disclosure. Audit committee and profitability have a positive and significant effect on sustainability report disclosure. Liquidity and leverage have a positive and significant effect on profitability. The audit committee has no effect on profitability. Profitability is successful in mediating the indirect effect of liquidity and leverage on sustainability report disclosure. However, profitability has failed in mediating the indirect influence between the audit committee on sustainability report disclosure. The conclusion of this study is liquidity, leverage, audit committee, and profitability have an important role in disclosure of sustainability report.